Estudantes mulheres com altas habilidades/superdotação na educação superior - Belotti, Kamila Caldeira (Universidade Federal de São Carlos, 2025)
This Final Course project investigated the academic and socio-emotional experiences of five adult women assessed as giftedness in Brazilian higher education. The type of research undertaken was descriptive qualitative. Five gifted students participated, two undergraduate and three graduate students, who responded to a questionnaire. The results obtained were: a) none of the participants were recognized institutionally or offered any type of specialized support by the university; b) the participants were identified in adulthood (average age of 26.6 years); c) they reported boredom, intellectual underchallenge, extreme self-pressure, impostor syndrome, social isolation, unanimous preference for individual work, and pursuit of extracurricular activities as their only source of stimulation; and d) it was found that although the three dimensions (above-average ability, creativity, and engagement with the task) are present in the participants, they feel a lack of inclusive practices and gender stereotypes. It is concluded that there is an urgent need to create services to identify these students in higher education and provide specialized support; viable and legally guaranteed measures that can transform exclusion into a true flourishing of female talent.
Gifted female students in higher education
Keywords: Educação especial; Altas habilidades/superdotação; Mulheres; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 5. Igualdade de Gênero